Pengaruh Citra Merek terhadap Minat Pembelian Somethinc - Riski Andalan Lase; Ujang Yusup (Universitas 45 Surabaya, 2025)
This research is designed to assess how brand perception influences consumers' willingness to buy Somethinc items. The study employs a quantitative approach by conducting a survey among individuals who have prior knowledge of Somethinc products. A total of 105 participants were selected for the research sample through purposive sampling, which is a non-probability sampling technique. The information gathered was examined using multiple linear regression methods. The results of this analysis reveal that the brand image significantly affects consumer interest in Somethinc products, and the overall perception of the brand contributes to the intention to purchase.